Coexistence of Allergic Diseases in Pediatric Systemic Lupus Erythematosus Patients: Prevalence, Clinical manifestation and Severity - Porntipa Suebsarakam MD; Kitiporn kaweeyanont MD; Sureeporn Srisutthikamol APN; Dara Mairiang MD (SAGE Publishing, 2024)
Objective . This study aimed to evaluate allergic diseases in pediatric patients with SLE and their association with SLE disease activity. Method . Patients with SLE aged ≤18 years were enrolled. Allergic diseases were screened using the International Study of Asthma and Allergies in Childhood questionnaire. Patients with a positive allergic disease screen were evaluated by a pediatric allergist for diagnostic confirmation and severity assessment. Results . Out of 118 patients, 16 patients (13.56%) were confirmed to have 1 or more allergic diseases; fourteen with allergic rhinitis, 4 with asthma, and 2 with atopic dermatitis. Two patients had severe-persistent allergic rhinitis and one patient had undiagnosed, uncontrolled severe asthma. No statistically significant correlations between the severity of allergic diseases and SLE disease activity were identified. Conclusions . The overall prevalence of allergic disease among pediatric patients with SLE is within the range of the general population. Severe and undiagnosed allergic diseases and SLE can coexist.